EAP-Based Instructional Material For Agriculture - Perado, Marlon L. (International Journal of Global Community, 2019)
Reading is the cornerstone for a student’s success in school and throughout life. Thisstudy delved on EAP-based Instructional Materialfor Agriculture.Itexaminedthe reading skills and competencies of Senior High School students of the Technical-Vocational-Livelihood (TechVoc)track in Agri-fishery Arts strand in the three campusesof Pangasinan State University and came out with an instructional material for agriculture. The descriptive research method was used in this study. Findings showed that the Senior High School studentslack mastery of reading skills. The developed instructional material for Senior High Schoolis validas to its face, content, and readability.